2018
DOI: 10.1155/2018/1508637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aortic Intimal Hyperplasia and Vascular Smooth Muscle Proliferation and Extracellular Matrix Protein Expressions by Astragalus–Angelica Combination

Abstract: VSMC proliferation and ECM deposition always resulted in intimal hyperplasia. Astragalus–Angelica combination has a protective effect on the cardiovascular system. The inhibition effect of different Astragalus–Angelica combination on the hyperplastic intima after vascular balloon injury in rats was investigated in this study. Astragalus–Angelica combination can inhibit the intima hyperplasia after balloon injury, in which a 1:1 ratio shows excellent results. Astragalus–Angelica combination can enhance the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…AGE, the receptor for AGE (RAGE) binding, activated the expression of MMP-9 [ 19 ]. Yan et al [ 20 ] reported that Milkvetch root- Angelica combination inhibited the expression of MMP-9. In this study, yixintongmai inhibited the migration of VSMCs and the expression of MMP-9 induced by high glucose, suggesting the inhibition of MMP-9 expression may be one of the potential mechanisms of anti-atherosclerotic effects of yixintongmai.…”
Section: Discussionmentioning
confidence: 99%
“…AGE, the receptor for AGE (RAGE) binding, activated the expression of MMP-9 [ 19 ]. Yan et al [ 20 ] reported that Milkvetch root- Angelica combination inhibited the expression of MMP-9. In this study, yixintongmai inhibited the migration of VSMCs and the expression of MMP-9 induced by high glucose, suggesting the inhibition of MMP-9 expression may be one of the potential mechanisms of anti-atherosclerotic effects of yixintongmai.…”
Section: Discussionmentioning
confidence: 99%
“…e actin cytoskeleton could be affected in glomerular disease [20,21]. A growing number of papers have shown that the cytoskeleton is injured by oxidative stress and can be restored by Chinese herbs [22,23]. Moreover, Chinese herbs also have a positive effect on the podocyte cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…AGE-the receptor for AGE (RAGE) binding activated the expression of MMP-9 (Bongarzone, et al, 2017). Yan et al (Yan, et al, 2018) reported that astragalus-angelica combination inhibited the expression of MMP-9. In this study, yixintongmai inhibited the migration of VSMCs and the expression of MMP-9 induced by high glucose, suggesting the inhibition of MMP-9 expression may be one of the potential mechanisms of antiatherosclerotic effects of yixintongmai.…”
Section: Discussionmentioning
confidence: 99%